Application of O / P composite phase manganese-based material as sodium ion battery positive electrode sodium supplementing agent, preparation method, positive electrode active material and sodium ion battery

By adding O/P composite phase manganese-based material to the sodium ion battery positive electrode material as a sodium supplementing agent, the problem of structural damage and performance degradation in the charge and discharge cycle of the sodium ion battery positive electrode material is solved, and the battery has high cycle stability and long service life are achieved.

CN119650679APending Publication Date: 2025-03-18SHAOXING YUNENG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928405.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

钠离子电池正极材料在充放电循环中易受钠离子嵌入/脱出的体积变化影响,导致结构损伤和性能下降,且现有补钠剂在高电压下稳定性不足,相容性差,分布不均匀,导致电池循环稳定性差。

Method used

The O/P composite phase manganese-based material is used as the positive sodium supplementing agent for sodium ion batteries. Through the design of the core-shell structure, the compatibility and stability of the materials are improved, and the uniform distribution of the materials in the battery system is ensured through specific preparation methods.

Benefits of technology

It improves the specific capacity and capacity retention rate of the first charge of sodium ion batteries, enhances the cycle stability of the battery, extends the service life of the battery, and optimizes the performance of the battery at high voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650679A_ABST
    Figure CN119650679A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion battery materials, and discloses application of an O / P composite phase manganese-based material as a sodium ion battery positive electrode sodium supplementing agent, a preparation method, a positive electrode active material and a sodium ion battery. Firstly, the invention provides application of an O / P composite phase manganese-based material as a sodium ion battery positive electrode sodium supplementing agent; the O / P composite phase is of a core-shell structure, and the chemical expression of the core is Na Ni Fe < c > Mn < d > O < 2 >; and the chemical expression of the shell is NaxNiyMnzO2. The positive electrode active material containing the sodium supplementing agent can greatly improve the capacity and the cycling stability of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery materials, and in particular relates to a positive electrode material additive for a sodium ion battery. Background Art

[0002] Sodium-ion batteries have become a potential candidate to replace or supplement traditional lithium-ion batteries due to their advantages such as low cost, abundant resources and environmental friendliness. However, sodium ions still face some challenges in performance, especially in terms of the cycle stability and energy density of positive electrode materials. As a key component of sodium-ion batteries, the performance of positive electrode materials directly affects the overall performance of the battery. During the battery charge and discharge cycle, the positive electrode material undergoes volume changes caused by the insertion / extraction of sodium ions, which can easily cause structural damage and performance degradation. During the charge and discharge process of the battery, the positive electrode material will experience the insertion and extraction of sodium ions. This process may cause the volume expansion and contraction of the material, thereby causing damage to the material structure and performance attenuation, resulting in sodium ion loss. In addition, during the long-term cyclic use of the positive electrode material, as the sodium ions are gradually lost, the available capacity of the battery decreases, which means that the battery stores and releases less energy under the same charge and discharge conditions, thereby shortening the battery life.

[0003] In order to overcome the above problems, researchers are committed to developing various sodium cathode additives to improve the performance of sodium ion batteries. For the selection of sodium cathode additives, first, it is required to remove as much sodium ions as possible within the charging voltage range of the battery to avoid excessive sodium removal voltage causing decomposition of positive and negative electrode materials and electrolytes; second, it is required that the cathode additives themselves and the by-products after sodium removal have good chemical stability to ensure that they will not react with positive and negative electrode materials and electrolytes. There are many types of cathode sodium supplements that have been studied and reported, such as Na 3 P, Na 2 C 2 O 2 N 2 、Na 2 C 2 N 4 、Na 5 FeO 4 Although the existing cathode additives have improved the performance of sodium-ion batteries to a certain extent, there are still some limitations, such as poor compatibility of additives with cathode materials, insufficient stability of additives at high voltages, and uneven distribution of additives in the battery system, which leads to poor cycle stability of the battery. Summary of the invention

[0004] In view of the problems existing in the prior art, the main purpose of the present invention is to provide a sodium supplement. Secondly, the present invention provides a preparation method of the sodium supplement.

[0005] To achieve the above objectives, the present invention provides the following specific technical solutions.

[0006] In the first aspect, the present invention provides an application of an O / P composite phase manganese-based material as a positive electrode sodium supplement for a sodium ion battery; the O / P composite phase manganese-based material is a core-shell structure, and the chemical expression of the core is Na a Ni b Fe c Mn d O 2 , where 0.8<a<1.05, 0<b<1, 0<c<1, 0<d<1, b+c+d=1; the chemical expression of the shell is Na x Ni y Mn z O 2 , where 0.67<x<0.75, 0<y<1, 0<z<1, y+z=1.

[0007] In a further preferred embodiment, the mass of the shell is 1-15% of the mass of the core.

[0008] In a second aspect, the present invention provides a method for preparing an O / P composite phase manganese-based material, comprising: Mix nickel iron manganese hydroxide and sodium source and sinter to obtain Na a Ni b Fe c Mn d O 2 , where 0.8<a<1.05, 0<b<1, 0<c<1, 0<d<1, b+c+d=1; Will Na a Ni b Fe c Mn d O 2 adding into an ethanol solution containing a sodium source, a nickel source and a manganese source, stirring, evaporating to dryness, and drying to obtain a precursor; The precursor is calcined to obtain an O / P composite phase manganese-based material.

[0009] In a further preferred embodiment, the molar ratio of Ni, Fe and Mn in the nickel-iron-manganese hydroxide includes but is not limited to 1:1:1, 2:1:1, 2.5:1:1 and 3:1:1.

[0010] In a further preferred embodiment, when the nickel-iron-manganese hydroxide and the sodium source are mixed, the molar ratio of the nickel-iron-manganese hydroxide and the sodium in the sodium source is 1:0.8-1.05.

[0011] In a further preferred embodiment, the sintering temperature is 650-1100°C.

[0012] In a further preferred embodiment, the sodium source is at least one of sodium carbonate, sodium hydroxide, sodium nitrate, sodium acetate and sodium oxalate.

[0013] In a further preferred embodiment, the nickel source is at least one of nickel acetate, nickel hydroxide and nickel nitrate.

[0014] In a further preferred embodiment, the manganese source is at least one of manganese acetate, manganese oxide and manganese oxalate.

[0015] In a further preferred embodiment, the molar ratio of Na, Ni and Mn in the ethanol solution is 0.67~0.75:0.25~0.75:0.25~0.75.

[0016] In a further preferred embodiment, the calcination temperature is 650-1000°C.

[0017] Based on the same inventive concept, the present invention provides a positive electrode active material for a sodium ion battery, comprising the aforementioned O / P composite phase manganese-based material.

[0018] Furthermore, the mass proportion of the O / P composite phase manganese-based material in the positive electrode active material is 1-3%.

[0019] In addition, the present invention provides a sodium ion battery comprising the aforementioned positive electrode active material.

[0020] The beneficial effects of one or more technical solutions of the present invention will be reflected through the following specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XRD pattern of the final product obtained in Example 1.

[0022] Figure 2 This is the SEM image of the final product obtained in Example 1. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0024] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0025] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0026] Example 1 (1) First weigh 11.87 g of nickel iron manganese hydroxide (NiFeMn(OH) 2 ) and 5.29 g of sodium carbonate (Na 2 CO 3 ) were put into a mortar for grinding and mixing, and then moved to a ball mill for ball milling at 800 rpm. The ball-milled mixture was calcined at 650°C for 24 hours in a tube furnace under air atmosphere and cooled to room temperature to obtain the core material.

[0027] (2) Weigh 1.517 g of sodium carbonate (Na 2 CO 3 ), 0.742 g nickel acetate (Ni(CH 3 COO 2 ) and 2.418 g manganese acetate ((CH 3 COO 2 Mn) were mixed in a mortar and added to 100 ml of anhydrous ethanol for 30 min of ultrasonication, followed by stirring at 200 rpm to dissolve to obtain a coating solution. 5 g of core material was weighed and added to the coating solution and continued to stir at room temperature for 30 min, then heated to 120 °C, stirred and evaporated, and placed in a vacuum drying oven at 120 °C for 10 h.

[0028] (3) The dried material was sintered in a muffle furnace at 650 °C for 24 h and then cooled to obtain the final product.

[0029] The final product of this example was analyzed by X-ray powder diffraction. Figure 1 The final product has O3 phase and P2 phase, indicating that the O / P composite phase manganese-based material was successfully prepared.

[0030] The final product of this embodiment was scanned using a scanning electron microscope, and the result was as follows: Figure 2 The final product is an irregular secondary sphere with a diameter of about 2 μm.

[0031] Comparative Example 1 Weigh 11.87 g of nickel iron manganese hydroxide (NiFeMn(OH) 2 ) and 5.29 g of sodium carbonate (Na 2 CO 3 ) were put into a mortar for grinding and mixing, and then moved to a ball mill for ball milling at 800 rpm. The ball-milled mixture was calcined at 650° C. for 24 h in a tube furnace under air atmosphere and cooled to room temperature to obtain the final product.

[0032] Comparative Example 2 Weigh 1.517 g of sodium carbonate (Na 2CO 3 ), 0.742 g nickel acetate (Ni(CH 3 COO 2 ) and 2.418 g manganese acetate ((CH 3 COO 2 Mn) were mixed evenly in a mortar, added to 100 ml of anhydrous ethanol and ultrasonicated for 30 min, and then stirred at 200 rpm to dissolve to obtain a mixed solution. The solution was then stirred and evaporated at 120°C and placed in a vacuum drying oven at 120°C for 10 h. The dried material was sintered in a muffle furnace at 650°C for 24 h, and the temperature was lowered to obtain the final product.

[0033] Comparative Example 3 First, weigh 1.8 g of sodium carbonate (Na 2 CO 3 ), 1.25g of nickel oxide (NiO), 1.25g of iron oxide (Fe 2 O 3 ) and 0.57 g of manganese dioxide (MnO) were ground and mixed in a mortar, then moved to a ball mill and ball milled at 500 rpm for 6 h. The ball-milled mixture was calcined at 750 ° C for 12 h in a tube furnace under nitrogen atmosphere and cooled to room temperature to obtain the final product.

[0034] Example 2 (1) First weigh 14.76 g of nickel iron manganese hydroxide (NiFe 0.5 Mn 0.5 (OH) 2 ) and 4.6g of sodium hydroxide (NaOH) were put into a mortar and ground and mixed, and then moved to a ball mill and ball milled at 900rpm. The ball-milled mixture was calcined at 850℃ for 24h in a tube furnace under air atmosphere and cooled to room temperature to obtain the core material.

[0035] (2) Weigh 2.8 g of sodium hydroxide (NaOH), 2.32 g of nickel hydroxide (Ni(OH) 2 ), 5.32g of manganese oxide (MnO) was mixed evenly in a mortar, added to 100ml of anhydrous ethanol and ultrasonicated for 30 min, then stirred and dissolved at 200rpm to obtain a coating solution. 5g of core material was weighed and added to the coating solution and stirred at room temperature for 30min, then heated to 120℃, stirred and evaporated the solution and placed it in a vacuum drying oven at 120℃ for 10h.

[0036] (3) The dried material is sintered in a muffle furnace at 800 °C for 24 h and then cooled to obtain the final product.

[0037] Example 3 (1) First weigh 28.153 g of nickel iron manganese hydroxide (Ni 2.5 FeMn(OH) 2 ) and 9.35 g of sodium nitrate (NaNO 3 ) were put into a mortar for grinding and mixing, and then moved to a ball mill for ball milling at 950 rpm. The ball-milled mixture was calcined at 1050°C for 24 h in a tube furnace under air atmosphere and cooled to room temperature to obtain the core material.

[0038] (2) Weigh 6.3 g of sodium nitrate (NaNO 3 ), 4.5 g nickel nitrate (Ni(NO 3 ) 2 ), 10.7 g manganese oxalate (MnC 2 O 4 ) were mixed in a mortar and added to 100 ml of anhydrous ethanol for 30 min of ultrasonication, followed by stirring at 200 rpm to dissolve to obtain a coating solution. 5 g of core material was added to the coating solution and stirred at room temperature for 30 min, then heated to 120 °C, stirred, evaporated, and placed in a vacuum drying oven at 120 °C for 10 h.

[0039] (3) The dried material is sintered in a muffle furnace at 950 °C for 24 h and then cooled to obtain the final product.

[0040] Example 4 (1) First weigh 17.646 g of nickel iron manganese hydroxide (Ni 1.5 Fe 0.5 Mn 0.5 (OH) 2 ) and 8.61 g of sodium acetate (CH 3 COONa) was put into a mortar for grinding and mixing, and then moved to a ball mill for ball milling at a speed of 1000 rpm. The ball-milled mixture was calcined at 700°C for 24 hours in a tube furnace under air atmosphere and cooled to room temperature to obtain the core material.

[0041] (2) Weigh 5.4 g of sodium acetate (CH 3 COONa), 8.8 g nickel acetate (Ni(CH 3 COO 2 ), 8.6 g manganese acetate (Mn(CH 3 COO 2 ) were mixed in a mortar and added to 100 ml of anhydrous ethanol for 30 min of ultrasonication, followed by stirring at 200 rpm to dissolve to obtain a coating solution. 5 g of core material was added to the coating solution and stirred at room temperature for 30 min, then heated to 120 °C, stirred, evaporated, and placed in a vacuum drying oven at 120 °C for 10 h.

[0042] (3) The dried material is sintered in a muffle furnace at 700 °C for 24 h, and then cooled to obtain the final product.

[0043] Example 5 (1) First weigh 11.878 g of nickel iron manganese hydroxide (NiFeMn(OH) 2 ) and 7.37 g of sodium oxalate (Na 2 C 2 O 4 ) were put into a mortar for grinding and mixing, and then moved to a ball mill for ball milling at 800 rpm. The ball-milled mixture was calcined at 800°C for 24 hours in a tube furnace under air atmosphere and cooled to room temperature to obtain the core material.

[0044] (2) Weigh 8.6 g of sodium oxalate (Na 2 C 2 O 4 ), 8.8 g nickel acetate (Ni(CH 3 COO 2 ), 7.1g manganese oxide (MnO) was mixed evenly in a mortar, added to 100ml anhydrous ethanol and ultrasonicated for 30 min, then stirred and dissolved at 200rpm to obtain a coating solution. 5g core material was weighed and added to the coating solution and stirred at room temperature for 30min, then heated to 120℃, stirred and evaporated the solution and placed in a vacuum drying oven at 120℃ for 10h.

[0045] (3) The dried material is sintered in a muffle furnace at 850 °C for 24 h and then cooled to obtain the final product.

[0046] Example 6 (1) First weigh 14.76 g of nickel iron manganese hydroxide (NiFe 0.5 Mn 0.5 (OH) 2 ) and 5.93 g of sodium carbonate (Na 2 CO 3 ) were put into a mortar for grinding and mixing, and then moved to a ball mill for ball milling at 900 rpm. The ball-milled mixture was calcined at 900°C for 24 hours in a tube furnace under air atmosphere and cooled to room temperature to obtain the core material.

[0047] (2) Weigh 12.8 g of sodium carbonate (Na 2 CO 3 ), 9.1 g nickel hydroxide (Ni(OH) 2 ), 7.1 g manganese oxalate (MnC 2 O 4) were mixed in a mortar and added to 100 ml of anhydrous ethanol for 30 min of ultrasonication, followed by stirring at 200 rpm to dissolve to obtain a coating solution. 5 g of core material was weighed and added to the coating solution, which was stirred at room temperature for 30 min, then heated to 120 °C, stirred, evaporated, and placed in a vacuum drying oven at 120 °C for 10 h.

[0048] (3) The dried material is sintered in a muffle furnace at 900 °C for 24 h, and then cooled to obtain the final product.

[0049] Example 7 (1) First weigh 28.15 g of nickel iron manganese hydroxide (Ni 2.5 FeMn(OH) 2 ) and 9.69 g of sodium nitrate (NaNO 3 ) were put into a mortar for grinding and mixing, and then moved to a ball mill for ball milling at a speed of 950 rpm. The ball-milled mixture was calcined at 1000°C for 24 hours in a tube furnace under air atmosphere and cooled to room temperature to obtain the core material.

[0050] (2) Weigh 5.6 g of sodium nitrate (NaNO 3 ), 13.7g nickel nitrate (Ni(NO 3 ) 2 ), 4.3 g manganese acetate ((CH 3 COO 2 Mn) were mixed in a mortar and added to 100 ml of anhydrous ethanol for 30 min of ultrasonication, followed by stirring at 200 rpm to dissolve to obtain a coating solution. 5 g of core material was weighed and added to the coating solution and continued to stir at room temperature for 30 min, then heated to 120 °C, stirred and evaporated, and placed in a vacuum drying oven at 120 °C for 10 h.

[0051] (3) The dried material is sintered in a muffle furnace at 950 °C for 24 h and then cooled to obtain the final product.

[0052] Example 8 (1) First weigh 17.64 g of nickel iron manganese hydroxide (Ni 1.5 Fe 0.5 Mn 0.5 (OH) 2 ) and 9.26 g of sodium acetate (CH 3 COONa) was put into a mortar for grinding and mixing, and then moved to a ball mill for ball milling at a speed of 1000 rpm. The ball-milled mixture was calcined at 650°C for 24 hours in a tube furnace under air atmosphere and cooled to room temperature to obtain the core material.

[0053] (2) Weigh 5.8 g of sodium acetate (CH3 COONa), 13.26 g nickel acetate (Ni(CH 3 COO 2 ), 4.76g of manganese oxide (MnO) was mixed evenly in a mortar, added to 100ml of anhydrous ethanol and ultrasonicated for 30 minutes, then stirred and dissolved at 200rpm to obtain a coating solution. 5g of core material was weighed and added to the coating solution and stirred at room temperature for 30 minutes, then heated to 120℃, stirred and evaporated the solution and placed it in a vacuum drying oven at 120℃ for 10 hours.

[0054] (3) The dried material was sintered in a muffle furnace at 650 °C for 24 h and then cooled to obtain the final product.

[0055] Test Case Test Example 1 Weigh 0.016 g of the final product of Example 1, 0.784 g of the positive electrode material (the final product of Comparative Example 3), 0.1 g of acetylene black (conductive agent), and 0.1 g of PVDF (HSV900, binder), grind them thoroughly, add 6 mL of NMP to disperse and mix, slurry them evenly, and then draw them on aluminum foil to make sheets. After drying at 85°C with air blast, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use a metal sodium sheet as the counter electrode and 1 M NaPF 6 The solution (solvent EC:DEC volume ratio of 1:1) was used as the electrolyte, and glass fiber (Grade GF / F) was used as the separator to assemble a CR2032 button cell. The battery was heated at 25°C with a charge of 1Ag -1 The constant current charge and discharge test was carried out at a rate between 2-4.0V.

[0056] Test Example 2 The only difference between Test Example 2 and Test Example 1 is that 0.008 g of the final product of Example 1 and 0.792 g of the positive electrode material (the final product of Comparative Example 3) were weighed.

[0057] Test Example 3 The only difference between Test Example 3 and Test Example 1 is that 0.024 g of the final product of Example 1 and 0.776 g of the positive electrode material (the final product of Comparative Example 3) were weighed.

[0058] Test Comparative Example 1 The difference between Comparative Example 1 and Test Example 1 is that the final product of Comparative Example 1 replaces the final product of Example 1.

[0059] Test Comparative Example 2 The only difference between Comparative Example 2 and Test Example 1 is that the final product of Comparative Example 2 replaces the final product of Example 1.

[0060] Test Comparative Example 3 The difference between Comparative Example 3 and Test Example 1 is that Na 3 P replaces the final product of Example 1.

[0061] Test Comparative Example 4 The difference between Comparative Example 4 and Test Example 1 is that: 2 C 2 O 2 N 2 The final product of Example 1 was replaced.

[0062] Test Comparative Example 5 The difference between Comparative Example 5 and Test Example 1 is that: 2 C 2 N 4 The final product of Example 1 was replaced.

[0063] Test Comparative Example 6 The difference between Comparative Example 6 and Test Example 1 is that: 5 FeO 4 The final product of Example 1 was replaced.

[0064] Test Comparative Example 7 The difference between Test Example 7 and Test Example 1 is that 0 g of the final product of Example 1 and 0.08 g of the positive electrode material (the final product of Comparative Example 3) are weighed.

[0065] Test Example 4 Weigh 0.016 g of the final product of Example 2, 0.784 g of the positive electrode material (the final product of Comparative Example 3), 0.1 g of acetylene black (conductive agent), and 0.1 g of PVDF (HSV900, binder), grind them thoroughly, add 6 mL of NMP to disperse and mix, slurry them evenly, and then draw them on aluminum foil to make sheets. After drying at 85°C with air blowing, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use a metal sodium sheet as the counter electrode and 1 M NaPF 6 The solution (solvent EC:DEC volume ratio of 1:1) was used as the electrolyte, and glass fiber (Grade GF / F) was used as the separator to assemble a CR2032 button cell. The battery was heated at 25°C with a charge of 1Ag -1 The constant current charge and discharge test was carried out at a rate between 2-4.0V.

[0066] Test Example 5 Weigh 0.016 g of the final product of Example 3, 0.784 g of the positive electrode material (the final product of Comparative Example 3), 0.1 g of acetylene black (conductive agent), and 0.1 g of PVDF (HSV900, binder), grind them thoroughly, add 6 mL of NMP to disperse and mix, slurry them evenly, and then draw them on aluminum foil to make sheets. After drying at 85°C with air blowing, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use a metal sodium sheet as the counter electrode and 1 M NaPF 6 The solution (solvent EC:DEC volume ratio of 1:1) was used as the electrolyte, and glass fiber (Grade GF / F) was used as the separator to assemble a CR2032 button cell. The battery was heated at 25°C with a charge of 1Ag -1 The constant current charge and discharge test was carried out at a rate between 2-4.0V.

[0067] Test Example 6 Weigh 0.016 g of the final product of Example 4, 0.784 g of the positive electrode material (the final product of Comparative Example 3), 0.1 g of acetylene black (conductive agent), and 0.1 g of PVDF (HSV900, binder), grind them thoroughly, add 6 mL of NMP to disperse and mix, slurry them evenly, and then draw them on aluminum foil to make sheets. After drying at 85°C with air blowing, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use a metal sodium sheet as the counter electrode and 1 M NaPF 6 The solution (solvent EC:DEC volume ratio of 1:1) was used as the electrolyte, and glass fiber (Grade GF / F) was used as the separator to assemble a CR2032 button cell. The battery was heated at 25°C with a charge of 1Ag -1 The constant current charge and discharge test was carried out at a rate between 2-4.0V.

[0068] Test Example 7 Weigh 0.016 g of the final product of Example 5, 0.784 g of the positive electrode material (the final product of Comparative Example 3), 0.1 g of acetylene black (conductive agent), and 0.1 g of PVDF (HSV900, binder), grind them thoroughly, add 6 mL of NMP to disperse and mix, slurry them evenly, and then draw them on aluminum foil to make sheets. After drying at 85°C with air blowing, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use a metal sodium sheet as the counter electrode and 1 M NaPF 6 The solution (solvent EC:DEC volume ratio of 1:1) was used as the electrolyte, and glass fiber (Grade GF / F) was used as the separator to assemble a CR2032 button cell. The battery was heated at 25°C with a charge of 1Ag -1 The constant current charge and discharge test was carried out at a rate between 2-4.0V.

[0069] Test Example 8 Weigh 0.016 g of the final product of Example 6, 0.784 g of the positive electrode material (the final product of Comparative Example 3), 0.1 g of acetylene black (conductive agent), and 0.1 g of PVDF (HSV900, binder), grind them thoroughly, add 6 mL of NMP to disperse and mix, slurry them evenly, and then draw them on aluminum foil to make sheets. After drying at 85°C with air blowing, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use a metal sodium sheet as the counter electrode and 1 M NaPF 6 The solution (solvent EC:DEC volume ratio of 1:1) was used as the electrolyte, and glass fiber (Grade GF / F) was used as the separator to assemble a CR2032 button cell. The battery was heated at 25°C with a charge of 1Ag -1 The constant current charge and discharge test was carried out at a rate between 2-4.0V.

[0070] Test Example 9 Weigh 0.016 g of the final product of Example 7, 0.784 g of the positive electrode material (the final product of Comparative Example 3), 0.1 g of acetylene black (conductive agent), and 0.1 g of PVDF (HSV900, binder), grind them thoroughly, add 6 mL of NMP to disperse and mix, slurry them evenly, and then draw them on aluminum foil to make sheets. After drying at 85°C with air blowing, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use a metal sodium sheet as the counter electrode and 1 M NaPF 6 The solution (solvent EC:DEC volume ratio of 1:1) was used as the electrolyte, and glass fiber (Grade GF / F) was used as the separator to assemble a CR2032 button cell. The battery was heated at 25°C with a charge of 1Ag -1 The constant current charge and discharge test was carried out at a rate between 2-4.0V.

[0071] Test Example 10 Weigh 0.016 g of the final product of Example 8, 0.784 g of the positive electrode material (the final product of Comparative Example 3), 0.1 g of acetylene black (conductive agent), and 0.1 g of PVDF (HSV900, binder), grind them thoroughly, add 6 mL of NMP to disperse and mix, slurry them evenly, and then draw them on aluminum foil to make sheets. After drying at 85°C with air blowing, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use a metal sodium sheet as the counter electrode and 1 M NaPF 6 The solution (solvent EC:DEC volume ratio of 1:1) was used as the electrolyte, and glass fiber (Grade GF / F) was used as the separator to assemble a CR2032 button cell. The battery was heated at 25°C with a charge of 1Ag -1 The constant current charge and discharge test was carried out at a rate between 2-4.0V.

[0072] The battery performance test results are shown in Table 1.

[0073] Table 1 As can be seen from Table 1, the O / P composite phase manganese-based material provided by the present invention is added to the active material as a sodium-filling agent for the positive electrode of sodium electricity, which can make the battery have a higher initial charge specific capacity and a higher capacity retention rate. The test results of Test Example 1, Test Example 2 and Test Example 3 show that the addition amount of the O / P composite phase manganese-based material as a sodium-filling agent is in the range of 1~3%, and the battery has a higher initial charge specific capacity and capacity retention rate, and when the addition amount is 2%, the battery performance is better. The data of Test Comparative Example 7 show that when the sodium-filling agent is not added to the positive electrode material, the initial charge and discharge specific capacity and capacity retention rate of the battery are both low, and the battery performance is poor. The data of Test Example 1 and Test Comparative Examples 1~6 show that the O / P composite phase manganese-based material as a sodium-filling agent for the positive electrode material of sodium electricity can better improve the initial charge specific capacity and capacity retention rate of the battery compared to other materials, and the O / P composite phase manganese-based additive is a sodium-filling positive electrode additive with better structural stability and sodium compensation effect. In addition, the batteries of Test Examples 2 to 10 also have a higher initial charge and discharge specific capacity and a higher capacity retention rate.

[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An application of an O / P composite phase manganese-based material as a positive electrode sodium supplement for sodium ion batteries, characterized in that: The O / P composite phase is a core-shell structure, and the chemical expression of the core is Na a Ni b Fe c Mn d O2, where 0.8<a<1.05, 0<b<1, 0<c<1, 0<d<1, b+c+d=1; the chemical expression of the shell is Na x Ni y Mn z O2, where 0.67<x<0.75, 0<y<1, 0<z<1, y+z=1.

2. The use according to claim 1, characterized in that The mass of the shell is 1-15% of the mass of the core.

3. A method for preparing an O / P composite phase manganese-based material, characterized in that: include: Mix nickel iron manganese hydroxide and sodium source and sinter to obtain Na a Ni b Fe c Mn d O2, where 0.8<a<1.05, 0<b<1, 0<c<1, 0<d<1, b+c+d=1; Will Na a Ni b Fe c Mn d O2 is added to an ethanol solution containing a sodium source, a nickel source, and a manganese source, stirred, evaporated, and dried to obtain a precursor; The precursor is calcined to obtain an O / P composite phase manganese-based material.

4. The preparation method according to claim 3, characterized in that: The molar ratio of Ni, Fe and Mn in the nickel-iron-manganese hydroxide includes but is not limited to 1:1:1, 2:1:1, 2.5:1:1 and 3:1:1; When the nickel-iron-manganese hydroxide and the sodium source are mixed, the molar ratio of the nickel-iron-manganese hydroxide and the sodium in the sodium source is 1:0.8-1.

05.

5. The preparation method according to claim 3 or 4, characterized in that: The sintering temperature is 650-1100°C.

6. The preparation method according to claim 3, characterized in that: The sodium source is at least one of sodium carbonate, sodium hydroxide, sodium nitrate, sodium acetate, and sodium oxalate; The nickel source is at least one of nickel acetate, nickel hydroxide and nickel nitrate; The manganese source is at least one of manganese acetate, manganese oxide, and manganese oxalate; The molar ratio of Na, Ni and Mn in the ethanol solution is 0.67-0.75:0.25-0.75:0.25-0.

75.

7. The preparation method according to claim 3, characterized in that: The calcination temperature is 650-1000°C.

8. A positive electrode active material for a sodium ion battery, characterized in that: The invention comprises an O / P composite phase manganese-based material prepared by the preparation method according to any one of claims 3 to 7.

9. The positive electrode active material for a sodium ion battery according to claim 8, characterized in that The mass proportion of the O / P composite phase manganese-based material in the positive electrode active material is 1-3%.

10. A sodium ion battery, characterized in that: Comprising the positive electrode active material according to claim 8 or 9.